High-Performance and Self-Powered Alternating Current Ultraviolet Photodetector for Digital Communication - Kumar, Mohit; Park, Ji Yong; Seo, Hyungtak (ACS Applied Materials and Interfaces, 2021)
Self-powered ultraviolet photodetectors offer great potential in the field of optical communication, smart security, space exploration, and others; however, achieving high sensitivity with maintaining fast response speed has remained a daunting challenge. Here, we develop a titanium dioxide-based self-powered ultraviolet photodetector with high detectivity (≈1.8 × 1010 jones) and a good photoresponsivity of 0.32 mA W-1 under pulsed illumination (λ = 365 nm, 4 mW cm-2), which demonstrate an enhancement of 114 and 2017%, respectively, due to the alternating current photovoltaic effect compared to the conventional direct current photovoltaic effect. Further, the photodetector demonstrated a high on/off ratio (≈103), an ultrafast rise/decay time of 112/63 μs, and a noise equivalent power of 5.01 × 10-11 W/Hz1/2 under self-biased conditions. Photoconductive atomic force microscopy revealed the nanoscale charge transport and offered the possibility to scale down the device size to a sub-10-nanometer (∼35 nm). Moreover, as one of the practical applications, the device was successfully utilized to interpret the digital codes. The presented results enlighten a new path to design energy-efficient ultrafast photodetectors not only for the application of optical communication but also for other advanced optoelectronic applications such as digital display, sensing, and others.
Keywords: Alternating current; Atomic-force-microscopy; Digital communications; High-performing; Performance; Photoconductive atomic force microscopy; Security space; Self-powered; Ultra-fast; Ultra-violet photodetectors; digital communication; high-performing; photoconductive atomic force microscopy; self-powered; ultraviolet photodetectors